Lecturers Room Navigation : UTHM Pagoh - Kassim, Noordiana; Awang Khalib, Nor Athirah; Abdul Aziz, Nur Fatihah Areesha; Zamzuri, Sofiah Sabihah (Multidisciplinary Applied Research and Innovation, 2020)
‘Lecturer’s Room Navigation’ is a mobile application used to navigate direction in the building for Universiti Tun Hussein Onn Malaysia (UTHM) students. The application can be used by Android users. The problem occur because of the complex building that locate room for each lecturers. Besides that, the room number are very complicated to understand and it is confusing because of there are so many door to enter and exit. Getting lost is a comman thing that happen among students especially new students that are not used to which wing either. Because of that, ‘Lecturer’s Room Navigation’ were built to help students in finding their lecturer’s room without getting lost. With the implementation of texts and images, it is easier to understand and students just follow the instructions given. Students can choose their starting point to start which is lobby, stairs and lift. For this project, ADDIE Model would be chosen as the methodology model for the development of our project. Five phase in model by order Analysis, Design, Development, Implementation and Evaluation for the process of development. In conclusion, it is hope that this application is the greatest technology provided that can help people in finding direction better.